1990
DOI: 10.1017/s0022112090001318
|View full text |Cite
|
Sign up to set email alerts
|

Lunate-tail swimming propulsion. Part 2. Performance analysis

Abstract: The theory of an oscillating, high-aspect-ratio, lifting surface with a curved centreline (Cheng & Murillo 1984) is applied to a performance analysis of lunate-tail swimming propulsion. Thrust, power and propulsive efficiency are calculated for model lunate tails with various combinations of mode shapes and morphological features to ascertain the viability of the proportional-feathering concept, and to determine the influence of sweep and centreline curvature. One of the principal conclusions concerns the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 14 publications
(23 reference statements)
2
35
0
2
Order By: Relevance
“…The moderate aspect ratio, three-dimensional foil in Martin et al [80] produced steady and unsteady lift forces comparable to those experienced by the two-dimensional foil employed by Read et al [98]. This demonstrates once more that end-effects are less important in unsteady foils than steady foil, in accordance with the findings in [51], [14], and [25].…”
Section: E Maneuvering Foilssupporting
confidence: 70%
See 2 more Smart Citations
“…The moderate aspect ratio, three-dimensional foil in Martin et al [80] produced steady and unsteady lift forces comparable to those experienced by the two-dimensional foil employed by Read et al [98]. This demonstrates once more that end-effects are less important in unsteady foils than steady foil, in accordance with the findings in [51], [14], and [25].…”
Section: E Maneuvering Foilssupporting
confidence: 70%
“…The effect of the aspect ratio on the forces is reduced as the reduced frequency increases, because the tip vortices are of alternating sign, hence the induced velocities are significantly reduced. This observation, first made by Karpouzian et al [51], was also reported in the numerical study of Cheng et al [14]. Recent detailed data on three-dimensional foils [80] show little degradation of propulsive performance for moderate aspect ratio foils, compared with the results for two-dimensional foils.…”
Section: B Steadily Oscillating Three-dimensional Foilssupporting
confidence: 69%
See 1 more Smart Citation
“…The lunate planform has been shown to be efficient in analytical models of unsteady, low amplitude propulsion (Lighthill, 1970;Cheng and Murillo, 1984;Karpouzian et al, 1990), originally applied to bony fish, sharks, whales and dolphins. The rigidity of the wings may indicate an attempt to maintain this efficient shape in straight and turning flight.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of a small local angle of attack along a flapping wing is analogous to control of the proportional feathering parameter identified by Lighthill (Lighthill, 1969;Lighthill, 1970) for efficient propulsion in oscillating fins, and extended to threedimensional geometries (Karpouzian et al, 1990). In birds, St is allowed to vary with U, so that both f and A can be maintained almost constant.…”
Section: What Fixes the Strouhal Number?mentioning
confidence: 99%